2021
DOI: 10.1177/11206721211020644
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of spectral domain optical coherence tomography in the diagnosis of posterior vitreous detachment in vitreomacular interface disorders: A prospective cohort study

Abstract: Purpose: To evaluate the sensitivity of Spectral Domain Optical Coherence Tomography (SD-OCT) regarding the diagnosis of posterior vitreous detachment (PVD) in vitreomacular interface disorders (VID). Methods: A total of 48 eyes of 48 patients were included in this prospective cohort study. PVD in eyes with VID was investigated. We determined the status of posterior vitreous cortex using slit lamp (SL) biomicroscopy and SD-OCT preoperatively, during vitrectomy and on the intraoperative video recording. Sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 24 publications
3
23
2
Order By: Relevance
“…The main finding in this study is that preoperative OCT may not be sufficiently sensitive to detect the status of the posterior hyaloid, which seems to imply that intraoperative TA staining is recommendable in most vitreoretinal pathologies. This confirms the findings described previously by Hwang et al 7 and Stavrakas et al 8 The new approach of this study is that we, for the first time, quantified the ability of OCT to diagnose PVD, compared to intraoperative TA-assisted assessment, which allowed us to estimate the sensitivity and specificity of this OCT-based diagnosis, in a range of retinal conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The main finding in this study is that preoperative OCT may not be sufficiently sensitive to detect the status of the posterior hyaloid, which seems to imply that intraoperative TA staining is recommendable in most vitreoretinal pathologies. This confirms the findings described previously by Hwang et al 7 and Stavrakas et al 8 The new approach of this study is that we, for the first time, quantified the ability of OCT to diagnose PVD, compared to intraoperative TA-assisted assessment, which allowed us to estimate the sensitivity and specificity of this OCT-based diagnosis, in a range of retinal conditions.…”
Section: Discussionsupporting
confidence: 89%
“…They also sought to identify minimally invasive imaging modalities that could be used reliably and efficiently in clinical settings for the detection of PVD, reporting that B-scan ultrasound was accurate but, importantly, operator-dependent. Similar observations were published by Muqit et al and Vaz-Pereira et al, 17,18 who evaluated the OCT features of neovascular complexes and correlated the results of an earlier study by Chu et al 19 Gupta et al found that vitreoschisis was present in 53% of patients with MH, as revealed by OCT. 20 Recently, Stavrakas et al 8 reported low sensitivity and specificity (37.5% and 31.3%) of spectral domain OCT in patients undergoing vitrectomy for diagnosis of ERM, MH and VMT. Although several studies have attempted to describe the findings in diabetic patients with ERM on time-domain OCT 21 and more recently on spectral-domain OCT, 22 our description of the intraoperative findings and poor specificity of OCT are consistent with a report by Gandorfer et al, 23 in which 60 of 61 eyes with diabetic macular edema (98.3%) and tangential VMT were examined with electron microscopy and showed native vitreous collagen overlying the macula.…”
Section: Discussionmentioning
confidence: 99%
“…As a part of preoperative preparation, all patients underwent complete systemic evaluation which included general laboratory ndings and a complete systemic examination to identify systemic diseases and drug use. In order to maximize the chance of achieving the appropriate vitreous evaluation, a complete preoperative ophthalmological assessment (BM, US and SD-OCT) was performed the day before surgery [8,13]. First independent investigator performed slit-lamp BM with fully dilated pupils using a 78D lens (Volk Optical Inc., Enterprise Drive Mentor, OH, USA).…”
Section: Methodsmentioning
confidence: 99%
“…First independent investigator performed slit-lamp BM with fully dilated pupils using a 78D lens (Volk Optical Inc., Enterprise Drive Mentor, OH, USA). A PVD was identi ed by the presence of a Weiss ring and or the de nitively detached visible posterior hyaloid membrane [8, 13,14]. It was classi ed as presence or absence of PVD on BM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation